Inovação e relações de cooperação: uma análise sobre o Programa de apoio à pesquisa em empresas (PAPPE) - Carrijo, Michelle de Castro (2011)
The thesis analyzes the Programa de Apoio à Pesquisa em Empresas (PAPPE), which emerged in Brazil in 2003 with the objective of supporting innovative projects developed by companies in partnership with researchers. It emerges as a political pioneer since it is a joint initiative of federal, via Financier of Studies and Projects (FINEP), and state sphere, via State Support Foundations (FAPs) with the intention to decentralize the actions to promote and provide resources to meet the needs and characteristics of regional development. Based on the neo-Schumpeterian theoretical framework, which supports a systemic view of the innovation process by developing the concept of national innovation system, the program, another groundbreaking project, aims to foster and strengthen relations of interaction between staff economic, since such relations can promote the generation and dissemination of knowledge and learning, highly interactive phenomena, which are key elements in the development and diffusion of innovations. The PAPPE is therefore one of the instruments used by the Brazilian government to try to overcome some bottlenecks that make the country‟s innovation system characterized by some scholars as immature/incomplete. Correspondingly, emerges the importance of studying it and identifying its contributions. For this, and through online interviews with participating companies of PAPPE, the present study considers the program in the States of Minas Gerais, Rio de Janeiro and Sao Paulo, in order to characterize these firms as well as identify their impacts on the interaction relationships and innovative activities. In general, companies that had projects approved in PAPPE are primarily young, created between 1990 and 2000; they are often small, and have a significant number of employees with higher education and graduate, has established partner relationships with other agents; have, in most cases, departments own R & D and founders originated the academic environment. That is, these companies point to the emergence of a new scenario in the country, which is formed by the micro and small innovative firms that recognize the importance of interaction relationships.